Investigating the Effects Of Sustainable Additives On The Performance And Microstructure Of Concrete - Thomas, Christopher Edwin; Saravanan, J.; Abiraami, R.; Kumar, R.Ganesh (Journal of Neonatal Surgery, 2025)
This research aims to explore the possibility of a dual binder system which is based on Fly Ash (FA) and Microcrystalline Cellulose Powder (MCC) as an alternative to Ordinary Portland Cement (OPC) concrete. The aim was to enhance both the mechanical and microstructural properties of concrete, and to increase sustainable construction practices. Concrete mixtures were designed to achieve a desired compressive strength of 30 MPa with w/c = 0.45. 10–25% of the cement was replaced by FA and 0.4–1.0% of MCC was added by the weight of the binder. The performance was evaluated in terms of the flexural strength, X-ray diffraction analysis (XRD), and bulk density. The blend with 15 wt% FA and 0.6 wt% MCC (M2) had best performance, with 5.5 MPa while 22.2% increase in flexural strength when compared to control mixture. Moreover, the density of M2 rose, implying denser microstructure. (2013) observed a decrease in the portlandite (Ca(OH)₂) peak intensity in mix M2, which suggested that a greater pozzolanic reaction was taking place. This reaction mechanism led to formation of additional C-S-H and enhanced both microstructure and strength. These findings demonstrate that FA with MCC-incorporated concrete can manufacture durable and sustainable concrete material containing high mechanical strengths. However the strengths and densities of specimens obtained by exceeding the optimal levels of FA and MCC, decreased, indicating the importance of dosage optimization. This study may provide an available route to develop green construction materials for sustainable infrastructure.